Entrepreneurial Opportunity And Collaborative Research Efforts As Panaceas For Improving Academic Entrepreneurship Among Ekiti State University Staff - Awolaja, Ayodeji. M. (Archives of Business Research, 2020)
The study assessed the impact of entrepreneurial opportunity and collaborative research efforts on academic entrepreneurship among Ekiti State University Staff. The study made use of prior entrepreneurial opportunity and collaborative research efforts as independent variables. The period of study was between 2017–2018. Descriptive survey research design was adopted and the research sample size of 100 was drawn from the total population of academic staff in all faculties in Ekiti State University through the adoption of Taro Yamane (1967) model. Convenience and purposive sampling techniques were adopted to select the sample that shares the same characteristics in order to ensure that every member of staff of all faculties was represented. Data were analysed using both descriptive and inferential statistics. The study revealed that entrepreneurial opportunity exerts positive impact on academic entrepreneurship among Ekiti state university staff and also, that collaborative research efforts exert positive impact on academic entrepreneurship among Ekiti state university staff.